Filming the atom: Systematically exploring images of nuclear energy and their messages in popular movies - Araripe Marinho, Cristóvão; Almeida Santos, Alberto; Vieira Neto, Julio; Quelhas, Osvaldo Luiz Gonçalves (Energy research & social science, 2021)
The objective of this study is to identify the depictions projected by films with regard to nuclear energy and the consequences of its image on the society. Based on a literature review related to the subject, we observed a contrarian approach to nuclear energy, which has led us to seek quantitative data to prove our initial perceptions. Thus, we analyzed a sample of 356 films, which had nuclear energy as the source of inspiration for storytelling. Consequently, we found that 96.35% of the films approached nuclear energy negatively, and only 3.65% were positive about it. With further investigation, we realized that cinema has long associated the nuclear field with danger and tragedy. By exposing the excessive negative approach that cinema has with regard to nuclear energy, we believe that this research contributes to repositioning society's perception of the subject, considering it on a more realistic level, conforming to a balanced and trend-free debate.